The Relationship Of Q.S Al-Alaq Verse 1 with Philosophy and Logic: - Aini, Qurrata; Fitriani, Adellia (Getpress Management Journals, 2023)
Philosophy, which is also called "the mother of sciences," uses reasoning and logic to explain various things and is able to answer all questions and problems. Likewise, the Al-Quran is a holy book whose every verse is able to be a solution to all the problems of Muslims. Therefore, this research focuses on finding out the relationship between Surah al-Alaq Verse 1 and aspects of philosophy and logic. This research method uses a philosophical framework that originates from the basic principles and teachings of the Koran. This research uses a literature review method. The results of the discussion in terms of philosophy and logic in Al-Alaq verse 1 are that questions such as: "Where do we come from?" “Who created us?” "Where is this universe from?" These questions are very radical, systematic and universal. These questions have been answered in QS Al-Alaq verse 1 which means: "In the name of God who created" So, the relationship of QS Al-Alaq verse 1 with philosophy and logic. In fact, this verse discusses reading as thinking and reading requires correct philosophy and correct logic. In this verse too, thinking philosophically, that is, getting to the roots, is what is called radical, so that we reach the point of thinking that this universe has a creator, namely Allah SWT. And Allah not only created the universe but also gave guidance to all mankind.